Incorporating variable lifetime and self‐discharge into optimal sizing and technology selection of energy storage systems. Issue 1 (20th April 2018) - Sayfutdinov, Timur; Patsios, Charalampos; Bialek, Janusz W.; Greenwood, David M.; Taylor, Phil C.
Abstract : Technology selection and sizing are key aspects of the design procedure for energy storage systems (ESSs) for power system applications. Here, the authors extended existing methodologies for optimal sizing and technology selection by introducing self‐discharge effects, and variable ESS lifetime as a function of energy throughput, which results in a non‐convex optimisation problem. Simulation results confirmed that making operational lifetime a variable has a significant impact on the results of the optimal sizing and technology selection problem. More specifically, considering the variable ESS lifetime as a function of energy throughput showed that ESSs of various technologies tend to operate such that their operational lifetimes would far exceed their calendar lifetimes. This has confirmed the importance of considering operational lifetime as a variable rather than a fixed value, as without doing this could result to underutilised and/or oversized systems. Taking into account, the self‐discharge effect showed that the electrochemical technologies considered here, with the exception of supercapacitors, have low levels of self‐discharge, which are largely obscured by the significant impact of the roundtrip efficiency characteristic.